PENGARUH KOMPENSASI NON FINANSIAL TERHADAP PRODUKTIVITAS KERJA KARYAWAN PT KRAKATAU DAYA LISTRIK (KDL) CILEGON BANTEN - Dadi Priadi (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Serang Raya, 2020)
This study aims to determine how is the iinfluence of non-financial compensation to productivity of PT Krakatau Daya Listrik (KDL) Cilegon Banten employee . Non-financial compensation consist of the satisfaction that a person receives from the job itself, or from the physical and psychological environment in which the person works. The author uses a quantitative approach with the Equation Modeling Structure analysis (SEM), with a population of 239 employees using the Slovin formula, then a sample of 71 employees was taken. The results showed non-financial compensation gave an effect of 83.8% on employee work productivity at PT Krakatau Daya Listrik (KDL) Cilegon, and the remaining 16.2% was influenced by other factors. Keywords: non-financial compensation, career or work, work environment, productivity